A review on the chemical constituents and pharmacological efficacies of Lindera aggregata (Sims) Kosterm - Lv, Yangbin; Zou, Yanfang; Zhang, Xindan; Liu, Bingrui; Peng, Xin; Chu, Chu (Frontiers in Nutrition, 2023)
Lindera aggregata (Sims) Kosterm (L. aggregata), which belongs to the genus Lindera in the family Lauraceae, is widely distributed in Asia and the temperate, tropical regions of North America. Its roots and leaves have been used for thousands of years as traditional Chinese medicine and/or functional food. To further explore its underlying nutritional value, this review provided a comprehensive insight into chemical constituents and pharmacological effects on L. aggregata. The phytochemical investigation of different parts of L. aggregata led to the identification of up to 349 components belonging to sesquiterpenoids, alkaloids, flavonoids, essential oils, and other compounds. Among them, sesquiterpenoids, flavonoids, and alkaloids are assessed as representative active ingredients of L. aggregata. A wide variety of pharmacological effects of L. aggregata, such as anti-hyperlipidemic, anti-tumor, anti-inflammatory, analgesic, and anti-oxidant, have been proved in vitro and in vivo. In summary, this review aims to provide a scientific basis and reference for further research and utilization of L. aggregata and lay the foundation for developing functional foods with potential active ingredients for the prevention and management of related diseases.